Effects of aromatherapy with Matricaria chamomile essential oil on anxiety and hemodynamic indices in patients with acute coronary syndrome, 2021: a randomized controlled trial - Majid Pourshaikhian; Mohammad Taghi Moghadamnia; Ehsan Kazemnezhad Leyli; Zahra Shafiei Kisomi (BMC Complementary Medicine and Therapies, 2024)
Abstract Background Patients with Acute Coronary Syndrome (ACS) experience high levels of anxiety that may cause instability of hemodynamic indices, increased risk of ischemia, myocardial infarction and poor quality of life. Aromatherapy can affect patients’ anxiety levels and improve hemodynamic indices. This study aimed to evaluate the efficacy of aromatherapy on anxiety and hemodynamic indices in ACS patients. Methods This study was a double-blind, randomized clinical trial conducted on 154 ACS patients. The participants were classified into two equal groups of intervention and placebo through the block randomization method. The data collection tools consisted of demographic information, a shortened 6-item version of the Spielberger questionnaire and a form of hemodynamic indices. For two consecutive nights, the intervention group inhaled 7 drops of the chamomile essential oil (%10) and the placebo group inhaled 7 drops of the sesame oil poured on a sterile cotton ball. The hemodynamic indices were collected half an hour before, one and four hours after the intervention until the next morning. The Spielberger questionnaire was completed once before the intervention and once after the end of the intervention, by the researcher through an interview. The number of heart rate (HR) was counted for a full minute. Also, the blood pressure (BP) of all the samples was measured by the researcher. Data analysis was done using Chi-square, paired t-test, and analysis of variance (ANOVA) in SPSS22. Results The mean and standard deviation of the age of patients were 58/2 ± 11.6 and 59.7% of them were female. The results of ANOVA showed a significantly lower anxiety score as well as systolic blood pressure (SBP), diastolic blood pressure (DBP) and HR in the intervention group compared to those of the placebo group (P < 0.001). The decrease in anxiety score after the intervention, in the intervention and placebo groups was (5.2 ± 1.9) and (1 ± 1. 18) respectively. In the intervention group, the SBP and DBP after the intervention, was significant (P < 0.05). Also, the HR was significant (P < 0.001) after the intervention. Conclusions Aromatherapy could reduce anxiety and improve hemodynamic indices in ACS patients. Trial registration IRCT20080825001083N11.